Risk factors and causes of adult deaths in the Ifakara health and demographic surveillance system population, 2003-2007 - Narh-Bana, Solomon Ayertey (My University, 2011)
Introduction: The achievements of the United Nations’ millennium development goals (MDGs) are not possible in isolation. Adult health and mortality with the exception of maternal health is one of the health issues that were openly missing among the list of MDGs. But eradicating extreme poverty and hunger would not be possible if the economically active population is not supported to be healthy and to live longer. Little has been done on adult health, especially to reduce mortality as compared to child health. Adult mortality is expected to equal or exceed child mortality in sub-Saharan Africa if nothing is done. There are varying factors associated with specific-causes of adult deaths within and among different settings. Obtaining more and better data on adult deaths and understanding issues relating to adult deaths in Africa are crucial for long life and development. Objectives: The study seeks to (i) describe causes of adult mortality, (ii) estimate adult cause-specific mortality rates and trends and (iii) identify risk factors of cause-specific mortality in the Ifakara Health and Demographic Surveillance System (IHDSS) population from 2003 – 2007 among adults aged 15 – 59 years. Methodology: The data for the study was extracted from the database of the Ifakara Health and Demographic Surveillance System (IHDSS) in Tanzania from 2003-2007. It was an open cohort study. The cohort was selected based on age (15-59years) and active residency from 1st January 2003 to 31st December 2007. Survival estimates were computed using Kaplan-Meier survival technique and adult mortality rates were estimated expressed per 1000 person years observed (PYO). Verbal autopsy method was used to ascertain causes of deaths. Cox proportional hazards method was used to identify socio-demographic factors associated with specific-causes of adult deaths. v Findings: A total 65,548 adults were identified and followed up, yielding a total of 184,000 person years. A total of 1,352 deaths occurred during the follow-up. The crude adult mortality rate (AMR) estimated over the period was 7.3/1000PYO. There was an insignificant steady increase in annual AMR over the period. The AMR in 2007 increased by 11% over year 2003. Most people died from HIV/AIDS (20.4%) followed by Malaria (13.2%). The AMR for the period was 2.49 per 1000PYO for communicable disease (CD) causes, 1.21 per 1000PYO for non communicable disease (NCD) causes and 0.53 per 1000PYO for causes related to accidents/injuries. Over the study period, deaths resulting from NCDs increased significantly by 50%. The proportion of deaths due to NCDs in 2003 was 16% increasing to 24% in year 2007. Adult deaths from Accidents/Injuries were significantly higher among men (hazard ratio (HR) = 2.2) after adjusting for socioeconomic status (SES), level of education and household size. For communicable and NCDs, most people died at home while for Accidents/Injuries most people died elsewhere (neither home nor health facility). The risk factors that were found to be associated with adult deaths due to NCDs were age and level of education. An improvement in level of education saw a reduction in the risk of dying from NCDs ((HR(Primary)=0.67, 95%CI:0.49, 0.92) and (HR(beyond Primary)=0.11, 95%CI:0.02, 0.40) after adjusting for age and sex. Age, SES and “entry type” were the factors found to be associated with dying from communicable diseases among the adults. In-migrants were 1.7 times more likely to die from communicable disease causes than residents having adjusted for age, household size, educational level, employment status of the head of household and SES. Conclusion: HIV/AIDS is the leading cause of adult deaths in IHDSS area followed by malaria. Most adult deaths occurred outside health facility in rural areas. This could probably be explained by the health seeking behavior and or health care accessibility in vi the rural area of sub-Saharan Africa. NCDs are increasing as a result of demographic and epidemiological transitions taking place in most African countries including Tanzania. Without preventions the rural community in Tanzania will soon face increased triple disease burden; (CD), NCD and Accident/Injuries. Policies on accident/injury preventions in developing countries will be effective if based on local evidence and research.
MSc (Med), Population-Based Field Epidemiology, School of Public Health, Faculty of health Sciences, University of the Witwatersrand
Keywords: adult deaths; risk factors; causes; Ifakara, Tanzania